CONNETTERE un disegno per annodare e tessere - CONNECTING drawing for weaving relationships Linguaggi Distanze Tecnologie - Languages Distances Technologies - Arena, Adriana; Arena, Marinella; Mediati, Domenico; Raffa, Paola (diségno, 2021)
The second volume dedicated to the 42nd International Conference of the Unione Italiana per il Disegno takes up the theme of 'Connecting' in reflecting on the topic Drawing: Languages, Distances, Technologies, also suggested by the remote condition that made it impossible for us to meet physically, and prompted and relaunched the conference itself. Languages, distances, technologies lead us to constantly review the dynamics that regulate the connections with drawing, and the historical and social context that in the last year and a half has characterized it. Drawing and visual Languages seen in the light of the multiple articulations that derive from them. Like a metaphor for language, drawing alludes, illudes, reveals and deceives. Drawing and Distances brings us to the practices of surveying, but also to the meaning of the word distancing, with all that it implies, to help us overcome the insurmountable physical separateness. Drawing and Technologies leads to the evidence of the digital world, viewed in its implications with the different sciences, transforming the computer from an instrument of calculation into an expressive source of communication, even artistic, for the development of a new digital aesthetic. In this volume, disciplines are intertwined, and even research sectors: a perfect path of contamination in which very different competencies come into play. And thus these three words, 'languages', 'distances', 'technologies', create a perfect circle that, rotating around drawing in a synchronous and often overlapping way, resumes and relaunches connections for creating new and ancient drawings.